Analisis Kelayakan Finansial Usaha Mebel di Desa Bangun Sari Kecamatan Lasalepa Kabupaten Muna - Karim, La Ode Mekar; Abdi, Abdi; Gafaruddin, Abdul (Department of Agribusiness, Halu Oleo University, 2019)
This study aims to determine the business feasibility and sensitivity of Sido Emerging Furniture Business. The study took place from January to May 2019. The data used in this study are primary data and secondary data. The technique of determining the data used is interviews, observation and documentation. The analysis used in this study is the analysis of NPV, NBCR, and IRR with a discount factor level of 12%. From the results of the study, the NPV value = Rp. 123,322,557, NBCR = 1.054, IRR = 36.39%. This shows that Usaha Mebel Sido Muncul in Bangunsari Village, Lasalepa Subdistrict, Muna Regency is feasible to cultivate. Likewise with sensitivity analysis if operational costs increase by 5% and revenues increase by 10% and sensitivity analysis if production falls and the price of production rises by 10% each which occurs jointly Sido Muncul Furniture business is still viable for business.